Pemanfaatan Media Sosial untuk Meningkatakan Brandingan dan Penjualan UMKM Warung Kue HJ. Risna di Kelurahan Karang Rejo - Pri Elma Tiana; Muhammad Rizkyansyah Ismail; Dini Aurora Ema Diva Sari; Alivia Rahmawati; Dede Pebrianto; Prawidha Surya Buana (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth and providing employment in Indonesia. However, many MSMEs are still utilizing digital technology to leverage social media as a marketing tool and strengthen their branding. This study aims to analyze the use of social media to increase product branding and sales at the Warung Kue HJ. Risna MSME, located in Karang Rejo Village, Balikpapan City. The research method used is a descriptive quantitative approach, with data collection techniques through field observations, direct interviews with MSME owners, and direct mentoring regarding social media use and online store creation. The results of this study indicate that improving social media accounts, creating business locations on Google Maps, and installing business banners with more attractive designs and colors can increase business visibility and understanding of the importance of branding through digital technology, positively impacting market expansion and potentially increasing business sales. This activity is expected to become a model for sustainable digitalization-based MSME mentoring to increase competitiveness in the era of digital transformation.